O uso da rede social de aprendizagem Edmodo como auxílio no processo de ensino-aprendizagem - Trova, Nilson Francischini (2014)
The use of computers and the Internet has become necessary in all sectors of society, including the education sector. The Internet has changed our ways of teaching and learning, accessing information and communicating. In this context, we wanted to investigate the use of these resources as tools to assist the teacher in the teachinglearning process. We assess the pedagogical potential of the Social Learning Network Edmodo, which has layout and functionality similar to Facebook and virtual learning environments. Within Edmodo we worked mainly with messaging and Learning Objects related to Dynamics, in the Physics course of high school students. We investigated the potential use of learning objects through forums where students discussed problem situations involving these resources. We observed that the use of the Social Learning Network Edmodo helped the teaching-learning process, motivating students and allowing them to develop critical thinking, acquire new skills and deepen already learned concepts. Besides the research with the students, we also present our impressions regarding the feasibility of using this tool from the point of view of other teachers, who participated in short courses on Edmodo.